Health profile of pediatric hospitalization for epilepsy in Brazil in the period between 2012 and 2022 (Research, Society and Development, 2024)
Objective: To evaluate the health profile of pediatric hospitalizations for epilepsy in the years 2012 to 2022. Methodology: Descriptive ecological study, using a time-series design, based on data available in the Hospital Information System of the Unified Health System (SIH/SUS), obtained through the Department of Informatics of the Unified Health System (Datasus). Results: The analyzed data between 2012 and 2022 revealed 231,450 epilepsy-related hospitalizations in Brazil, with the majority occurring in the Southeast region, followed by the Northeast, South, Midwest, and North regions. The most affected age group was 1 to 4 years, with a majority of male and mixed-race patients. The majority of hospitalizations were of an urgent nature, with an average length of stay of 4.9 days. Elective hospitalizations had a higher average length of stay, surpassing the overall average. During the study period, there were 1254 deaths related to pediatric epilepsy hospitalizations, with the majority of deaths occurring during urgent hospitalizations. Conclusions: Epilepsy primarily affects children in developing countries, causing abnormal brain electrical discharges capable of impairing development and quality of life. Investigations and studies, particularly in children, are essential for effective diagnostic, treatment, and support strategies aimed at controlling and preventing the disease, mitigating its impact on society.